Experimental studies on the behavior of concrete-filled uPVC tubular columns under axial compression loads. Issue 1 (1st January 2020) - Woldemariam, Abraham Mengesha; Oyawa, Walter O.; Nyomboi, Timothy
Abstract: The behavior of concrete-filled uPVC tubular columns under axial compression loads were studied experimentally by testing columns prepared from five different concrete strength classes. Accordingly, the unconfined, concrete-filled uPVC tube with and without wire-mesh reinforced mortar cover and reinforced concrete columns were evaluated. The main variables considered in this study are concrete strength, uPVC thickness to diameter ratio (2t/D) and aspect ratio (h/D). The effect of uPVC confinement on strength, ductility, energy absorption, and post-peak behavior was explored. Also, a model was developed to predict the peak strength. Results show that the uPVC confinement increased the strength, ductility, and energy absorption in between 1.28–2.35, 1.84–15.3, and 11–243 times the unconfined, respectively. The confinement performed well on increasing the strength, ductility, and energy absorption for lower concrete strength and higher 2t/D ratios. The post-peak behavior of the stress-strain curve was affected by 2t/D and h/D ratios; an abrupt drop in the stress-strain curve was observed in specimens with lower 2t/D and higher h/D ratio. For a given value of concrete strength, tensile strength, thickness (t), diameter (D), and height (h), the stress-strain model predicted the peak strength of axially loaded concrete-filled uPVC tube column with a mean absolute error of 2.7%.